In the Words of the Medical Tourist: An Analysis of Internet Narratives by Health Travelers to Turkey - Ozan-Rafferty, Margaret E; Johnson, James A; Shah, Gulzar H; Kursun, Attila (JMIR Publications, 2014)
BackgroundPatients regularly travel to the West for advanced medical care, but now the trend is also shifting in the opposite direction. Many people from Western countries now seek care outside of their country. This phenomenon has been labeled medical tourism or health travel. Information regarding health travelers' actual outcomes, experiences, and perceptions is lacking or insufficient. However, advanced Internet technology and apps provide information on medical tourism and are a vehicle for patients to share their experiences. Turkey has a large number of internationally accredited hospitals, is a top tourism destination, and is positioning itself to attract international patients. ObjectiveThe objective of this research was to identify the important individual characteristics of health travelers, outline the push and pull factors for seeking health care in Turkey, identify satisfaction with the outcomes and the results of these individuals' treatments, and note positive and negative factors influencing their perceptions and overall experiences about patients' health travel. MethodsThis research uses qualitative data from Internet narratives of medical tourists to Turkey. Ethical considerations of using Internet narratives were reviewed. Narratives for analysis were obtained by using the Google search engine and using multiple search terms to obtain publicly posted blogs and discussion board postings of health travelers via purposeful sampling. Narratives were included if they were written in English, described travel to Turkey for health care, and were publicly accessible. Exclusion criteria included narratives that were on medical tourism facilitator or provider promotional websites, not in English, and did not describe an experience of a medical tourist. Medical tourists' written words were analyzed in an iterative analytic process using narrative analysis theory principles. Three stages of coding (open, axial, and selective) were conducted to identify characteristics and themes using qualitative analysis software. ResultsThe narrative posts of 36 individuals undergoing 47 procedures who traveled to Turkey for medical care between 2007 and 2012 were analyzed. The narratives came from 13 countries, not including the narratives for which patient origin could not be determined. Travelers were predominantly from Europe (16/36, 44%) and North America (10/36, 28%). Factors driving travelers away from their home country (push factors) were cost and lack of treatment options or insufficient insurance coverage in their home country. Leading factors attracting patients to destination (pull factors) were lower costs, physician's expertise and responsiveness, and familiarity or interest in Turkey. Health travelers to Turkey were generally satisfied with the outcomes of their procedures and care provided by their physicians, many noting intent to return. Communication challenges, food, transportation, and gaps in customer service emerged as key areas for improvement. ConclusionsThis analysis provides an understanding of the insights of medical tourists through the words of actual health travelers. This nonintrusive methodology provides candid insights of common themes of health travelers and may be applied to study other patient experiences. The findings of this research expands the body of knowledge in medical tourism and serves as a platform for further qualitative and quantitative research on health travelers' experiences.